Diet of the neotropical otter Lontra longicaudis (Carnivora: Mustelidae) from the Santiago River basin, Mexico - Guerrero, Sergio; Zalapa, Silvia S.; Pérez-Arteaga, Alejandro; del Río-Vélez, Angélica E.; Camacho-Rodríguez, Agustín; Navarrete-Heredia, José Luis (Instituto de Ecología, A.C., 2018)
The diet of the neotropical otter Lontra longicaudis is reported in the Santiago River, Nayarit - Jalisco, Mexico. A diet based on fish was found (percentage of occurrence 43.86%), with lower frequencies of insects (22.81%), reptiles (9.36%) and amphibians (8.77%), with the introduced fish Oreochromis aureus and Cyprinus carpio, the most consumed.